The sensory experiences of autistic people: A metasynthesis. (July 2022) - Sibeoni, Jordan; Massoutier, Laura; Valette, Marie; Manolios, Emilie; Verneuil, Laurence; Speranza, Mario; Revah-Levy, Anne
Qualitative literature reports the sensory experiences of autistic individuals in the first person. Following a thematic synthesis procedure, this metasynthesis aimed to explore specifically the lived experience of these sensory features. Four databases were systematically searched for qualitative studies describing sensory issues reported by autistic individuals. Article quality was assessed with the Critical Appraisal Skills Programme. Thematic analysis was used to identify and synthesise key themes. The 32 articles included reported data from 430 participants. Data analysis produced two themes structuring the sensory experiences of autistic people: (1) the everyday experience through body, thoughts and emotions, and (2) the relational experience, relationships being experienced as both a problem and a solution. Four dimensions are found in our results: physical, emotional, relational and social. Whereas a scientific approach to the sensory experience of autistic people is based on a cause–effect model, our results suggest that autistic people experience these dimensions holistically, as inseparable, and not in terms of cause and effect. This original finding brings new research perspectives, beyond the dichotomy between sensory features and social communications issues, and concrete implications within the health care system to provide more effective and respectful care to autistic people. Lay abstract: Sensory atypicalities are very common among autistic people and are integrated in several theories and explanatory models of autism. Qualitative studies have explored these singular sensory experiences from the perspectives of autistic people themselves. This article gathers all these qualitative studies and provides original findings regarding the everyday sensory experience of autistic people, that is, around four dimensions – physical, emotional, relational and social – experienced holistically, as inseparable, and not hierarchically or in terms of cause and effect. Adopting this holistic view could improve the adaptation of the sensory environment in health care facilities and the training of professionals around this specific issue.